Intoxication with oral hypoglycemics as a cause of diffuse brain injury: case report Intoxicação com hipoglicemiante oral como causa de lesão cerebral difusa: relato de caso - Emerson L. Gasparetto; Leila Caroline Bianchet; Taisa Davaus; Arnolfo de Carvalho Neto (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To present the imaging findings of a patient with diffuse brain injury secondary to intoxication with oral hypoglycemics. CASE REPORT: A nine years-old boy presented with generalized tonic-clonic convulsions and decreased consciousness. Laboratory investigation demonstrated blood glucose level of 21 mg/dL. The magnetic resonance imaging showed cortical and subcortical temporo-parieto-occipital areas of high signal on T2 and low signal on T1, with high signal on the diffusion-weighted images and low signal on apparent diffusion coefficient maps. CONCLUSION: Cortical and subcortical temporal, parietal and occipital ischemic lesions may be seen in patients with intoxication by oral hypoglycemics. OBJETIVO: Apresentar os achados de imagem em um caso de lesão cerebral difusa secundária a intoxicação por hipoglicemiante oral. RELATO DE CASO: Menino de nove anos de idade apresentando crises convulsivas tônico-clônicas e rebaixamento do nível de consciência. Exames laboratoriais revelaram glicose sérica de 21 mg/dL. O exame de ressonância magnética revelou lesões corticais e subcorticais têmporoparieto-occipitais, com alto sinal em T2 e baixo em T1, apresentando hipersinal nas imagens ponderadas em difusão e hipossinal nos mapas de coeficiente aparente de difusão. CONCLUSÃO: Lesões isquêmicas corticais e subcorticais nos lobos temporais, parietais e occipitais podem ser identificadas em pacientes com intoxicação por hipoglicemiantes orais.